Pharmacoresistant epilepsy with electrical status epilepticus during slow-wave sleep: a clinical case - M. S. Maslov (Русский журнал детской неврологии)
The article presents a clinical case of epilepsy with electrical status epilepticus during slow-wave sleep, the example of which shows the relevance of the issue of timely diagnosis and prescription of adequate anti-epileptic therapy in this syndrome. The role of regular electroencephalographic sleep monitoring in order to monitor the effectiveness of therapeutic measures is emphasized, and the main difficulties in making this diagnosis and choosing the correct anti-epileptic treatment are shown.